A Systematic Literature Review on the Implementation of COBIT 2019 for IT Governance Evaluation - Nurul Asyikin Idrus; Sinta Nur Hidayati; Aris Puji Widodo (Journal of Renewable Energy, Electrical, and Computer Engineering, 2026)
The governance of information technology (IT) has become a crucial factor for organizations striving to achieve sustainability and a competitive advantage in the rapidly changing and dynamic business environment of today. The complexity of modern organizations demands the implementation of effective IT governance frameworks to manage technology resources efficiently. This study uses the Systematic Literature Review (SLR) method to evaluate the implementation of the COBIT 2019 framework in IT governance. Focusing on various organizations, this research aims to identify journal types, organizations that have adopted COBIT 2019, and the recommended governance domains to answer 3 Research Questions (RQ). A total of 62 articles from international and national databases were selected based on inclusion and exclusion criteria, resulting in 21 eligible articles from Scopus and SINTA. The findings indicate widespread adoption of COBIT 2019 across sectors, including education, healthcare, government and banking, with domain recommendations primarily focused on APO07, BAI03, BAI06, APO03, and APO12. These insights provide a valuable guide for organizations seeking to enhance IT governance in alignment with strategic goals.